A clinical and radiological investigation of patients with migraine and extensive white matter lesions - Hari, Kapila Ranchhodbhai (My University, 2014)
Eleven patients with chronic migrainous headaches and extensive white matter lesions as identified on Magnetic Resonance Imaging o f the brain were evaluated. The patients ranged in age from 28years to 62years. There were eight females and three males in our group. The patients were all o f Southern African descent. None o f the patients had a history o f migration from a high risk Multiple Sclerosis area. In terms o f racial configuration there were five patients o f Indian descent, four patients o f Mixed Ancestry and two patients who were o f Black African origin. There were no White patients in our group. The white matter lesions were identified on Magnetic Resonance Imaging and were found to be localized to the periventricular and subcortical white matter, corpus callosum and the basal ganglia. None of the patients had lesions in the brainstem, cerebellum or spinal cord. Clinically all the patients had a chronic history o f migraine and a positive family history for migraine. Each patient had at least one focal neurological event. All the patients suffered from depression. The patients were extensively investigated to exclude demyelination, dysmyelination, vasculitis/vasculopathy and other causes o f white matter lesions in the brain. No identifiable cause was elucidated. We concluded that the white matter lesions represent some kind o f vasculopathy. We can conclude that these patients have migraine with a vasculopathy which appears to be a distinct subtype o f migraine. They may represent a distinct disorder possibly a recessive form or a sporadic occurrence o f a CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy)-like disorder.
Thesis (M.Med. (Internal Medicine))--University of the Witwatersrand, Faculty of Health Sciences, 1998.